Attitutes of first entering students towards same-sex relationships at the University of Limpopo - Malatji, Lungile Cornellia (My University, 2016)
The South African constitution makes provision for the rights of gays and lesbians, and has legalized same-sex relationships. However, many people, including students in same-sex relationships continue to be harassed and maltreated. The purpose of this study was to examine the attitudes of first entering students towards same-sex relationships at the University of Limpopo. A sample of 100 students (first entering students= 50, final level students = 50; with ages ranging from eighteen to forty five years), with a total number of twenty five (25) students drawn each of the four faculties at the university were selected using a convenience sampling method. Data was collected using the Homophobia Scale comprising of 25 close-ended questions which focus on behavioural, affective and cognitive attitudes towards gays and lesbians. Data were analysed using nominal data analysis and interpreted using the Statistical Package for Social Scientists (SPSS) software. The study results revealed that fifty two percent (52%) of first entering students at the University of Limpopo have negative attitudes towards same-sex relationships with seventy four percent (74%) of first-entering students having no knowledge regarding same-sex relationships. Seventy three percent (73%) of participants behave negatively towards people in same-sex relationships. The study is concluded by recommending that more similar studies that include larger sample of students from different universities and different racial backgrounds be conducted. The results of the study have implications for the University of Limpopo in when it comes to understanding and promoting knowledge about same-sex relationships.
Thesis (M. A. (Clinical Psychology)) -- University of Limpopo, 2016
Keywords: Gays; Lesbians; Same-sex relationships; Sexual orientation; Homosexuality -- Social aspects; Gays -- South Africa -- Limpopo; Gays in higher education; Lesbians -- South Africa -- Limpopo